Market launch strategy of the brand Kiehl´s - Hartová, Dominika; Král, Petr, 1979-; Bihelerová, Judita; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The main aim of this diploma thesis is to suggest improvements of the marketing and business strategy of Kiehl's, a luxury skincare brand within the L'Oréal portfolio, in order to strengthen the brand's position on the Czech market. The theoretical part defines what luxury is and what the specific features of luxury brands are. Following is the overview of the luxury and cosmetics markets, describing the current situation and the trends. The next part depicts the business model of Kiehl's, the marketing strategy and the marketing tools that were used for the launch of the brand. Based on the findings in this thesis, a series of recommendations is suggested to build the brand's awareness, recruit new customers to the brand and increase sales.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses